Zona roja : la experiencia cubana del ebola - Ubieta Gomez, Enrique 1958- (Casa Editora Abril, 2016)
Zona Roja: La experiencia cubana del ébola (Red Zone: The Cuban Experience with Ebola) by Cuban journalist Enrique Ubieta. The book tells the story of the 256 volunteer Cuban doctors and nurses who served in West Africa in 2014 to combat the Ebola crisis. In individual testimonies, many of them describe the conditions created by the imperialist plunder of the region that contributed to the spread of the deadly epidemic. Their accounts also bring to life the selfless internationalist solidarity that has marked the Cuban Revolution from the beginning. Enrique Ubieta Gomez, who accompanied the Cubans to Africa, collected these firsthand accounts.